Multiple Cartilaginous Exostoses Causing Severe Cervical Myelopathy in a Puppy Dog - Menezes, Mareliza Possa de; Facin, Andréia Coutinho; Máximo, Larissa Godoi; Luzzi, Mayara de Cássia; Dias, Luis Gustavo Gosuen Gonçalves; Minto, Bruno Watanabe (VCOT Open, 2021)
This study aimed to report a case of multiple cartilaginous exostoses (MCE) causing severe cervical myelopathy in a puppy dog. An 80-day-old Dachshund cross weighing 2.2 kg presented with progressive development of non-ambulatory tetraparesis, proprioceptive ataxia in all four limbs, and cervical hyperesthesia. Multiple calcified masses in the cervical spine at the levels of C1–C2 and C4–C7, with several points of spinal cord compression, were identified. Ventral atlantoaxial fusion was performed. Four days later, four masses were surgically removed by dorsal laminectomy of C1–C2 and C4–C7, and a right facetectomy between C4 and C5 was performed. Multiple cartilaginous exostoses were confirmed by histopathological examination. Thirty-six months after surgery, the patient showed no recurrence of neurological signs. Ventral atlantoaxial fusion, and surgical removal of MCE masses followed by decompression was effective on alleviating clinical sings in the short and medium term.
Keywords: multiple cartilaginous exostosis; cervical spinal cord compression; hereditary neurological disorders; osteochondromatosis; atlantoaxial joint stabilization